1998
DOI: 10.1074/jbc.273.26.16415
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis by SB202190 through Inhibition of p38β Mitogen-activated Protein Kinase

Abstract: p38, a subfamily of the mitogen-activated protein kinase, regulates gene expression in response to various extracellular stimuli. The pyridinyl imidazoles like SB202190 are specific inhibitors of p38␣ and p38␤ and have been widely used in investigation of the biological functions of p38. Here we show that SB202190 by itself was sufficient to induce cell death, with typical apoptotic features such as nucleus condensation and intranucleosomal DNA fragmentation. SB202190 stimulated the activity of CPP32-like casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
216
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(234 citation statements)
references
References 58 publications
17
216
1
Order By: Relevance
“…p38g and SAPK4 were shown to phosphorylate predominantly transcription factors such as ATF-2 and were less e ective in phosphorylating MAPKAPK2 Goedert et al, 1997;Kumar et al, 1997). In addition, it has been reported that SB202190 was a speci®c inhibitor of p38a and p38b (Nemoto et al, 1998). Our study indicated that SB202190 signi®cantly suppressed UVB induced phosphorylation of MAPKAPK2, which implied that p38g and SAPK4 might play relatively less important roles compared to other p38 family members for UVB induced c-fos expression.…”
Section: Discussionmentioning
confidence: 55%
“…p38g and SAPK4 were shown to phosphorylate predominantly transcription factors such as ATF-2 and were less e ective in phosphorylating MAPKAPK2 Goedert et al, 1997;Kumar et al, 1997). In addition, it has been reported that SB202190 was a speci®c inhibitor of p38a and p38b (Nemoto et al, 1998). Our study indicated that SB202190 signi®cantly suppressed UVB induced phosphorylation of MAPKAPK2, which implied that p38g and SAPK4 might play relatively less important roles compared to other p38 family members for UVB induced c-fos expression.…”
Section: Discussionmentioning
confidence: 55%
“…Historically, sustained activation of p38MAPK is associated with apoptosis and conversely inhibition rescues cells from apoptotic death (Chang and Karin 2001;Mansouri et al 2003;Cai et al 2006;Zhou et al 2006;Tanel and Averill-Bates 2007). It should be noted that SB202190 inhibits both p38α and p38β and that p38α is pro-apoptotic whereas p38β MAPK isoform may be associated with activation of pro-survival pathways (Nemoto et al 1998). Indeed, a recent study by Caughlan et al (2004) demonstrated that CPF activates p38 MAPK and that SB202190 accelerates CPF-induced toxicity in cortical neurons.…”
Section: Discussionmentioning
confidence: 99%
“…At least four p38 subfamilies (α, β, γ and δ) have been isolated. P38-α induces, while p38-β suppresses cell death [36]. SB203580 inhibits mainly α and β isoforms [37,38].…”
Section: Discussionmentioning
confidence: 99%